Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) Berbasis Etnomatematika terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMPN 1 Bambanglipuro - Nuri Hidayati; Ahmad Anis Abdullah (Jurnal Tadris Matematika, 2021)
The ability to solve problems is a basic ability which is one of the goals of learning mathematics. Contextual Teaching and Learning (CTL) based on ethnomathematics can be a solution to improve students' mathematical problem solving abilities with a cultural approach around students. This study aims to determine the effectiveness of the application of ethnomathematical-based CTL model on the mathematical problem solving abilities of class VIII students of SMP N 1 Bambanglipuro. This research is a quantitative research with a quasi-experimental type. The design of this research is non-equivalent control group design. The population in this study were all eighth grade students of SMP N 1 Bambanglipuro for the 2020/2021 academic year. Purposive sampling technique used to select class VIII A as the control class, conducted 24 students, and class VIII C as the experimental class, conducted 24 students. The instrument used to determine the level of student problem solving is in the form of Prisma essay test material. The data analysis technique used is the average difference test using the t-test. The results showed that the average mathematical problem solving of students with the ethnomathematics-based CTL model was more than the average mathematical problem solving of students with conventional learning. Thus it can be said that the application of ethnomathematical-based CTL is effective in solving students' mathematical problems.